Harvard business review on strategic renewal (Harvard Business School Pub., 2008)
Technologies, consumer preferences and market dynamics are changing faster than ever. To help their companies stay competitive in the face of accelerating change, leaders need to continually test and redefine their strategies. This book provides the ideas readers need to refresh their competitive strategy.